Sodium ferric sulfate composite positive electrode material and preparation method and application thereof
Through vacuum crushing and isopressurized sintering technology, the structure of the iron sodium sulfate composite cathode material is optimized, the problem of material performance deterioration in the prior art is solved, the charge and discharge capacity and Coulomb efficiency are improved, and the electrochemical performance is improved.
Patent Information
- Application Number
- CN202411390338.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The preparation process of existing sodium ion battery positive electrode materials leads to insufficient bonding between conductive carbon and sodium ferrosulfate, resulting in deterioration of material performance, especially low compaction density, large specific surface area, and inappropriate void ratio, which affects the charge and discharge capacity and the first time. efficiency.
The iron and sodium sources are crushed under vacuum conditions, and then mixed and sintered isobaric. Combined with conductive carbon and antioxidants, the porosity, compaction density and specific surface area of the iron sulfate composite material are optimized through isobaric sintering technology to reduce the rich Sodium heterophase content improves conductivity.
The porosity, compaction density and specific surface area of the sodium iron sulfate composite cathode material have been optimized, the charge and discharge capacity and first-time Coulomb efficiency have been improved, the electrochemical performance has been improved, and the water absorption and impurity content have been reduced.
Smart Images

Figure CN119252898A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium iron sulfate composite positive electrode material and a preparation method and application thereof. Background Art
[0002] Limited by the existing preparation process of sodium ion positive electrode materials, the combination of conductive carbon and sodium iron sulfate in sodium ion positive electrode materials is not tight enough, which is not conducive to the performance of the material.
[0003] The positive electrode materials of sodium ion batteries include layered oxides, Prussian white, and polyanion materials. Among them, polyanion materials have stable structure, high working voltage, good safety performance, high cycle stability and high specific capacity, and have attracted widespread attention. Iron-based sulfate is a resource-rich polyanion material, which contains Fe 3+ / Fe 2+ Reversible redox couple and SO4 2- Due to its strong electronegativity and inductive effect, it has the advantages of low production cost and high working voltage (3.0-3.8V), so it can be used as a positive electrode material for sodium ion batteries. However, polyanionic materials have poor conductivity and often need to be carbon-coated to obtain positive electrode materials for sodium ion batteries with excellent electrochemical properties.
[0004] However, due to the limitations of the existing preparation process, the carbon-coated iron-based sulfate and other sodium-ion battery positive electrode materials have low compaction density, large specific surface area, and inappropriate porosity, which deteriorates their first coulombic efficiency, charge and discharge specific capacity and other performance.
[0005] For example, among the existing methods for preparing sodium ferric sulfate, such as solid-phase method, solvent thermal reaction method, anti-solvent method, spray drying method, freeze drying method, etc., the solid-phase method has a simple process and is easy to operate, so the research on the solid-phase method is the most in-depth. In the solid-phase method, the crushing and mixing of materials are mostly achieved by ball milling, but due to the limitations of the ball mill itself, the mixing uniformity of the materials is not sufficient, and because the sintering temperature for preparing sodium ferric sulfate cannot be too high, basically not exceeding 350°C, so at a lower sintering temperature, atoms are difficult to diffuse, resulting in insufficient reaction of the various phases, poor product consistency, low compaction density, and a high content of miscellaneous items in the prepared sodium ferric sulfate, which in turn leads to low electrochemical performance.
[0006] Therefore, a sodium iron sulfate composite positive electrode material with excellent porosity, compaction density and specific surface area is relatively lacking in the field. Summary of the invention
[0007] The invention provides a sodium ferric sulfate composite positive electrode material and a preparation method and application thereof. The sodium ferric sulfate composite positive electrode material has excellent porosity, compacted density and specific surface area, and low sodium-rich impurity content, which helps to improve its charge and discharge capacity, first coulomb efficiency and other performances.
[0008] The present invention provides a sodium iron sulfate composite positive electrode material, wherein the porosity of the sodium iron sulfate composite positive electrode material is 0.1% to 10%, and the compaction density is 2.1 to 3 g / cm 3 , and the specific surface area of the sodium iron sulfate composite positive electrode material is 5 to 12 m 2 / g, and the mass percentage of the sodium-rich impurity phase in the sodium iron sulfate composite positive electrode material is 0.1% to 1%.
[0009] Optionally, in an atmosphere with a humidity of 0.1 to 0.5 ppm, the rate of increase of the water content of the sodium ferric sulfate composite positive electrode material is lower than 5.5 ppm / h; in an atmosphere with a humidity of less than 0.1 ppm, the rate of increase of the water content of the sodium ferric sulfate composite positive electrode material is lower than 2.5 ppm / h; and / or, the mass percentage of trivalent iron in the sodium ferric sulfate composite positive electrode material is lower than 1%; and / or, the mass percentage of impurities in the sodium ferric sulfate composite positive electrode material is lower than 5%.
[0010] Optionally, the chemical formula of the sodium iron sulfate composite positive electrode material is Na 2+2x Fe 2-x (SO4)3@C, where 0≤x<2.
[0011] Optionally, the particle size of the primary particles of the sodium iron sulfate composite positive electrode material is 50 to 1000 nm, and some of the primary particles agglomerate to form secondary particles, and the particle size of the secondary particles is 1 to 10 μm; in the sodium iron sulfate composite positive electrode material, the mass percentage of the secondary particles is 15% to 40%, and the mass percentage of the remaining primary particles is 60% to 85%.
[0012] Optionally, the sodium iron sulfate composite positive electrode material also includes conductive carbon; among the secondary particles, some secondary particles are formed by agglomeration of the primary particles connected by the conductive carbon, the mass percentage of the some secondary particles in the secondary particles is 15% to 40%, and the mass percentage of the remaining part of the secondary particles in the secondary particles is 60% to 85%.
[0013] The present invention provides a method for preparing the sodium ferric sulfate composite positive electrode material as described above, comprising the following steps: respectively crushing an iron source and a sodium source to a particle size of less than 1 μm; mixing the crushed iron source, the crushed sodium source, conductive carbon and an antioxidant to obtain a precursor; drying the precursor under vacuum conditions, sealing the dried precursor to ensure that the precursor is under vacuum conditions, and then isobaric sintering the sealed precursor, wherein the isobaric sintering pressure is 1 to 500 MPa, the temperature is 300 to 400° C., and the time is 1 to 24 hours to obtain the sodium ferric sulfate composite positive electrode material.
[0014] Optionally, after mixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant, the process of obtaining the precursor includes: premixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant, crushing and mixing them again with a jet mill or a rolling ball mill, and finally using a planetary ball mill or a vibrating ball mill for solid solution mixing to obtain the precursor; and / or, the isostatic sintering includes hot isostatic pressing sintering or spark plasma sintering; and / or, during the isostatic sintering process, the heating rate is 1 to 5°C / min.
[0015] Optionally, the iron source includes ferrous sulfate; and / or the sodium source includes sodium sulfate; and / or the conductive carbon includes one or more of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, redox graphene, acetylene black, Ketjen black, carbon nanofibers, activated carbon; and / or the antioxidant includes one or more of ascorbic acid, citric acid, tea polyphenols, and glucose; the ratio of the mass of the antioxidant to the mass of the iron source is 0.01% to 10%.
[0016] The present invention also provides a positive electrode sheet, which comprises the sodium iron sulfate composite positive electrode material as described above or the sodium iron sulfate composite positive electrode material obtained according to the preparation method as described above.
[0017] The present invention also provides a sodium ion battery, comprising the positive electrode sheet as described above.
[0018] The invention provides a sodium ferric sulfate composite positive electrode material and a preparation method and application thereof. The sodium ferric sulfate composite positive electrode material has excellent porosity, compacted density and specific surface area, and has a low mass percentage of a sodium-rich impurity phase, which helps to improve the performance of the material, such as the charge and discharge capacity and the first coulomb efficiency, thereby improving the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the charge and discharge curve of Example 1-5;
[0020] Figure 2 1 is the charge and discharge curve of Example 1, Example 6 and Example 7;
[0021] Figure 3 The charge and discharge curves of Example 1 and Comparative Examples 1-3;
[0022] Figure 4 is the sodium ferric sulfate (Na 2.56 Fe 1.72 XRD pattern of (SO4)3);
[0023] Figure 5 This is the XRD diagram of the sodium-rich impurity phase (Na6Fe(SO4)4) in sodium iron sulfate in Comparative Example 1. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0025] The embodiment of the present invention provides a sodium iron sulfate composite positive electrode material, the porosity of the sodium iron sulfate composite positive electrode material is 0.1% to 10%, and the compaction density is 2.1 to 3 g / cm 3 , and the specific surface area of the sodium iron sulfate composite positive electrode material is 5 to 12 m 2 / g, and the mass percentage of the sodium-rich impurity phase in the sodium iron sulfate composite positive electrode material is 0.1% to 1%.
[0026] According to the research and analysis of the inventors: the porosity of the sodium iron sulfate composite positive electrode material in the embodiment of the present invention is 0.1% to 10%, so as to avoid excessive porosity limiting the electrochemical performance of the sodium iron sulfate composite positive electrode material, and the compaction density of the sodium iron sulfate composite positive electrode material is 2.1 to 3 g / cm 3 , specific surface area is 5~12m 2 / g, which helps to improve its first coulombic efficiency and charge-discharge specific capacity, thereby improving its electrochemical performance. In addition, the sodium-rich impurity phase helps to promote the transmission of sodium ions, which may be because the sodium-rich impurity phase can form a heterojunction with sodium ferric sulfate, serving as a fast ion channel to promote the transmission of sodium ions. However, an excessively high content of the sodium-rich impurity phase will inhibit the normal performance of the capacity of the sodium ferric sulfate, and will also lead to a significant reduction in the electrochemical performance of the sodium ferric sulfate composite positive electrode material. The mass percentage of the sodium-rich impurity phase in the sodium ferric sulfate composite positive electrode material of the embodiment of the present invention can be 0.1-1%, and a relatively low content of the sodium-rich impurity phase helps to improve the electrochemical performance of the sodium ferric sulfate composite positive electrode material.
[0027] The sodium iron sulfate composite positive electrode material of the embodiment of the present invention has weak water absorption. Specifically, in an atmosphere with a humidity of 0.1 to 0.5 ppm, the water content of the sodium iron sulfate composite positive electrode material increases at a rate lower than 5.5 ppm / h; in an atmosphere with a humidity of less than 0.1 ppm, the water content of the sodium iron sulfate composite positive electrode material increases at a rate lower than 2.5 ppm / h, which helps to improve the stability of its electrochemical performance. Thus, the problem of degradation of its electrochemical performance due to the strong water absorption of sodium iron sulfate is avoided.
[0028] In some embodiments, after the sodium iron sulfate composite positive electrode material is exposed to a drying room with a humidity of 0.01-0.1 ppm for 1 week, the moisture content thereof is less than 1000 ppm.
[0029] In some embodiments, the mass percentage of impurities in the sodium iron sulfate composite positive electrode material is less than 5%, that is, the purity of the sodium iron sulfate composite positive electrode material is relatively high.
[0030] The above impurities generally include manganese, zinc, calcium, trivalent iron, etc. The sources of these impurities include: the raw materials for preparing the sodium iron sulfate composite positive electrode material will carry impurities such as manganese, zinc, calcium, etc. In addition, during the preparation process, impurities accounting for less than 3% of the mass percentage of the sodium iron sulfate composite positive electrode material will also be introduced due to the wear and oxidation of instruments and equipment.
[0031] In addition, during the preparation process (sintering process), a sodium-rich heterophase (Na6Fe(SO4)4) is generated in the sodium iron sulfate composite positive electrode material. The sodium-rich heterophase helps to promote the transmission of sodium ions. This may be because the sodium-rich heterophase can form a heterojunction with sodium iron sulfate, which acts as a fast ion channel to promote the transmission of sodium ions. However, excessive content of the sodium-rich heterophase will inhibit the normal performance of the capacity of sodium iron sulfate, and will also cause the electrochemical performance of the sodium iron sulfate composite positive electrode material to be greatly reduced. Therefore, it is necessary to control the content of the sodium-rich heterophase at a lower level. The mass percentage of the sodium-rich heterophase in the sodium iron sulfate composite positive electrode material of the embodiment of the present invention can be 0.1% to 1%, and a lower content of the sodium-rich heterophase helps to improve the electrochemical performance of the sodium iron sulfate composite positive electrode material.
[0032] During the process of preparing the sodium iron sulfate composite cathode material, divalent iron is easily oxidized to trivalent iron. When the content of trivalent iron is too high, it will reduce the electrochemical performance of the sodium iron sulfate composite cathode material. However, in the sodium iron sulfate composite cathode material of the embodiment of the present invention, the mass percentage content of trivalent iron can be less than or equal to 1%, for example, 0.1% - 1%. The influence of the lower content of trivalent iron on the electrochemical performance of the sodium iron sulfate composite cathode material can be ignored.
[0033] In some embodiments, the chemical formula of the sodium iron sulfate composite cathode material is Na 2+2x Fe 2-x (SO4)3@C, where 0 ≤ x < 2. Combining sodium iron sulfate and conductive carbon helps improve the conductivity of the sodium iron sulfate composite cathode material, solves the problem of poor conductivity of sodium iron sulfate itself, and can also increase the specific surface area (BET) of the formed sodium iron sulfate composite cathode material and improve its electrochemical performance.
[0034] In addition, the above chemical formula can also be replaced by one or more of Formula 1, Formula 2, Formula 3, and Formula 4. Formula 1 is NaFe 1- x M x SO4F@C, where M = Ni, Co, Mn, etc., 0 < X ≤ 1; Formula 2 is Na x Fe y (PO4) a (SO4) b-z M c O d @C, where 0 < x ≤ 4, 0 < y ≤ 4, 0 < z ≤ 0.5, 0 < a ≤ 4, 0 < b ≤ 3, 0 < c ≤ 4, 0 < d ≤ 5; M is at least one of oxides, hydroxides, chlorides, nitrates, or carbonates of Ti, V, Cr, Mn, Fe, Co, Cd, Ni, Cμ, Zn, Al, Ag, Mg, Ca, Sn, or Se; Formula 3 is Na x Fe y (SO4) z , where 1 < x ≤ 10, 1 < y ≤ 10, z = x / 2 + y; Na x M y (SO4) z N n represents a sulfate, where x, y, z, and n are all positive real numbers, M includes Hf, Fe, and rare earth elements, and N includes Se and Cl; Formula 4 is Na a Fe b (SO4) c @C, where a + 2b = 2c, 0.3 ≤ a / b ≤ 2.8.
[0035] In some embodiments, the sodium iron sulfate composite positive electrode material is in a granular form, formed by combining conductive carbon and sodium iron sulfate materials, and the particle size of the primary particles of the sodium iron sulfate composite positive electrode material (conductive carbon composite sodium iron sulfate) is 50-1000nm, and some of the primary particles are agglomerated to form secondary particles, and the particle size of the secondary particles is 1-10μm. That is, the primary particles of the above-mentioned sodium iron sulfate composite positive electrode material particles can be divided into two parts, one part is agglomerated to form secondary particles, and the remaining part is not agglomerated to form secondary particles and exists alone.
[0036] There are many forms of conductive carbon in the sodium iron sulfate composite positive electrode material, including zero-dimensional conductive carbon, one-dimensional conductive carbon, and two-dimensional conductive carbon. These conductive carbons are partially distributed in a free state (free conductive carbon). Among them, zero-dimensional conductive carbon is point-like conductive carbon, such as super-p, carbon black, etc.; one-dimensional conductive carbon is linear conductive carbon, such as carbon nanofibers and carbon nanotubes; two-dimensional conductive carbon is sheet-like conductive carbon, such as graphene and graphene oxide. Free conductive carbon is the distribution state of conductive carbon. All conductive carbon that does not form a certain connection with the sodium iron sulfate matrix is free conductive carbon, and there is only physical contact between the free conductive carbon and the matrix material. The position of free conductive carbon in the sodium iron sulfate composite positive electrode material is not fixed, and stirring and ultrasound in the preparation process will change its position.
[0037] It can be seen that the surface of the primary particles is coated with conductive carbon in various forms.
[0038] In the sodium iron sulfate composite positive electrode material, the mass percentage of the above-mentioned secondary particles can be 15% to 40%, for example, 15%, 20%, 30%, 40% or a range consisting of any two thereof, the mass percentage of the remaining primary particles (primary particles that are not agglomerated to form secondary particles and exist alone) can be 60% to 85%, for example, 60%, 70%, 80%, 85% or a range consisting of any two thereof, and the mass percentage of free conductive carbon can be 0.1% to 3%, which helps to improve the porosity, compaction density and specific surface area of the sodium iron sulfate composite positive electrode material, and thus improve its electrochemical properties such as the first coulombic efficiency and charge and discharge specific capacity.
[0039] The secondary particles are mainly formed by the agglomeration of primary particles. The secondary particles can be divided into two parts according to the connection form. Some secondary particles are formed by the agglomeration of primary particles through conductive carbon. The connection of the above conductive carbon includes the winding and bonding of one-dimensional conductive carbon such as carbon nanotubes, and the coating and bonding of two-dimensional conductive carbon such as graphene, so that the conductive carbon is not only distributed at the interface between the primary particles, but also a large amount of conductive carbon is coated on the surface of the secondary particles. This coating is consistent with the form of the above-mentioned two-dimensional conductive carbon coating on the surface of the primary particles. The mass percentage of this part of secondary particles in the secondary particles can be 15% to 40%, and the remaining part of the secondary particles is mainly formed by the agglomeration of primary particles through mechanical intercalation and van der Waals bond connection. The mass percentage of the remaining part of the secondary particles in the secondary particles can be 60% to 85%, which is helpful to improve the porosity, compaction density and specific surface area of the sodium iron sulfate composite positive electrode material, and then improve its electrochemical properties such as the first coulomb efficiency and charge and discharge specific capacity.
[0040] The embodiment of the present invention also provides a method for preparing the above-mentioned sodium iron sulfate composite positive electrode material, comprising the following steps: respectively crushing the iron source and the sodium source to a particle size of less than 1 μm; mixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant to obtain a precursor; drying the precursor under vacuum conditions, sealing the dried precursor to ensure that the precursor is under vacuum conditions, and then isobaric sintering the sealed precursor, the isobaric sintering pressure is 1 to 500 MPa, the temperature is 300 to 400° C., and the time is 1 to 24 hours to obtain the sodium iron sulfate composite positive electrode material.
[0041] According to the inventor's research and analysis: crushing the iron source and the sodium source to a particle size D50 of less than 1 μm helps to promote uniform and sufficient mixing of the raw materials; sealing the precursor under vacuum conditions for isobaric sintering can not only prevent the oxidation of divalent iron to form trivalent iron, but also ensure that the reaction is fully carried out during the isobaric sintering process by applying pressure to the precursor during the sintering process and making the pressure on the precursor uniform and consistent, thereby ensuring that the purity of the sodium ferric sulfate composite positive electrode material is higher than 99%; in addition, by applying uniform and consistent pressure to the precursor during the isobaric sintering process, the sodium ferric sulfate and carbon are tightly combined, which can improve its porosity, thereby improving its compaction density and specific surface area, and can also solve the problem of strong water absorption of sodium ferric sulfate, effectively reduce the water absorption of the sodium ferric sulfate composite positive electrode material, and can further improve the conductivity of the sodium ferric sulfate composite positive electrode material by improving the combination of carbon and sodium ferric sulfate, thereby improving the first coulomb efficiency, charge and discharge specific capacity and other properties of the sodium ferric sulfate composite positive electrode material.
[0042] In specific implementation, mechanical milling and / or air flow milling can be used to crush the iron source and the sodium source to a particle size of less than 1 μm (controlled within 1 μm), wherein the iron source should be crushed under the protection of an inert gas. The embodiment of the present invention does not specifically limit the pressure and time of the above-mentioned air flow milling, as long as the particle size of the crushed iron source and the sodium source meets the requirements, for example, the pressure and time of the air flow milling can be 1.4-1.5 MPa and the time can be 8-10 min, and the inert gas can include nitrogen and / or argon.
[0043] Generally, the iron source and the sodium source can be vacuum dried before being crushed, for example, vacuum dried at 200-350°C for 1-15h. Before mixing various raw materials, the iron source and the sodium source are pre-crushed (crushed) respectively, and the D50 of the crushed iron source and the sodium source is made less than 1 μm, which is conducive to improving the uniformity of subsequent mixing.
[0044] The process of obtaining a precursor by mixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant includes: premixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant, crushing and mixing them again by air flow mill or rolling ball mill, and finally performing solid solution mixing by planetary ball mill or vibration ball mill to obtain the precursor.
[0045] It is understandable that in the above process of obtaining the precursor, inert gas protection is required.
[0046] In the specific implementation, the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant can be premixed in a high-speed mixer (high mixer), so that these materials can initially reach a relatively uniform state on a macroscopic level after premixing; then, an air flow mill or a rolling ball mill is used for crushing and mixing again, and the premixed materials are crushed (crushed) again to make the materials mixed more evenly, thereby achieving a higher uniformity on the microscopic level, which is beneficial to reducing the problem of component segregation; finally, a planetary ball mill or a vibrating ball mill is used for solid solution mixing, and the planetary ball mill or the vibrating ball mill can promote the prereaction of the iron source and the sodium source. Specifically, under the action of higher energy generated by high-energy ball mills such as planetary ball mills or vibrating ball mills, the iron source and the sodium source can undergo a prereaction, and the solid solution of the iron source and the sodium source and other phases (essentially the diffusion between atoms) is achieved, which is beneficial to the formation of a solid solution of the iron source and the sodium source, and reduces part of the diffusion energy barrier for the subsequent sintering reaction. The ball milling is used for crushing and mixing again, and the planetary ball milling or vibration ball milling is used for solid solution mixing. The synergistic effect of the uniform pressure provided by isobaric sintering promotes the diffusion of atoms, so that each material can fully react, thereby promoting the formation of the target phase (sodium ferric sulfate composite positive electrode material), thereby improving the purity of the sodium ferric sulfate composite positive electrode material to make its purity greater than 99%, and at the same time helps to improve the porosity, compaction density and specific surface area of the sodium ferric sulfate composite positive electrode material, as well as the first coulomb efficiency, charge and discharge specific capacity and other properties, avoiding the problems of organic solvent recovery and treatment environmental costs caused by wet ball milling using organic solvents, and organic solvent residues deteriorating the performance of positive electrode materials; solves the problem in the prior art that the degree of crushing of the raw materials is not sufficient and cannot reach the submicron level, which limits the uniformity of the mixing and the degree of reaction, and also avoids the problem of residual unreacted materials due to insufficient reaction, causing the segregation of the performance of the sodium ferric sulfate composite positive electrode material.
[0047] The premixing time of the above-mentioned high mixer can be 5 to 10 minutes; the airflow pressure of the airflow mill can be 0.5 to 1.5 MPa, and the time is 3 to 8 minutes; the ball-to-material ratio of the rolling ball mill is (15 to 25): 1, the rotation speed is 500 to 600 rpm, and the time is 22 to 26 hours; the ball-to-material ratio of the planetary ball mill is (8 to 12): 1, the rotation speed is 500 to 700 rpm, and the time is 4 to 8 hours; the vibration frequency of the vibration ball mill is 1400 to 1500 r / min, and the time is 4 to 6 hours.
[0048] The isostatic sintering may include hot isostatic pressing sintering or spark plasma sintering, preferably hot isostatic pressing sintering.
[0049] It is understandable that the sodium-rich impurity phase is difficult to completely remove. Although its content can be kept at a low level by adjusting the raw material ratio and process parameters (such as reducing the iron content), this phase is very easy to appear in the process of preparing sodium ferric sulfate with a high iron content according to the conventional method. Under the preparation method system provided in the embodiment of the present invention, isostatic sintering, preferably hot isostatic pressing sintering, is used to prepare a sodium ferric sulfate composite positive electrode material with a low content of sodium-rich impurity phase.
[0050] In addition, since the temperature in the sintering process for preparing sodium ferric sulfate cannot be too high, basically not exceeding 350°C, at a lower sintering temperature, atoms are difficult to diffuse, resulting in not only a longer reaction time for preparing sodium ferric sulfate, but also insufficient reaction between phases, poor consistency of sodium ferric sulfate, low electrochemical performance, and low compaction density. The embodiments of the present invention can appropriately reduce the sintering temperature and shorten the sintering time by adopting hot isostatic pressing technology, improve production efficiency, reduce energy consumption, improve the porosity of the sodium ferric sulfate composite positive electrode material, and then increase the compaction density of the sodium ferric sulfate composite positive electrode material, improve the specific surface area, and improve the electrochemical properties of the sodium ferric sulfate composite positive electrode material, such as the first coulomb efficiency and charge and discharge specific capacity.
[0051] During the hot isostatic pressing sintering process, the precursor can be loaded into a mold and dried under vacuum conditions, which can effectively reduce the moisture in the precursor and effectively inhibit the oxidation of divalent iron during the sintering process.
[0052] The vacuum condition can be a vacuum degree of 0.001 to 0.1 Pa, a drying temperature of 250 to 300° C., and a drying time of 0.5 to 2 h.
[0053] After the precursor is loaded into the mold, it can be compacted to not less than 1.0g / cm 3 , and then carry out subsequent drying processes.
[0054] Next, the dried precursor is sealed so that the precursor is always in a sealed state during the subsequent sintering process. On the one hand, the precursor is ensured to be in a vacuum condition, thereby effectively avoiding the problem of ferrous iron being oxidized during the subsequent treatment process. On the other hand, the precursor is prevented from contacting with water, effectively reducing the water absorption of the sodium iron sulfate composite positive electrode material. In specific implementation, the mold can be sealed or sealed to ensure that the precursor is in a vacuum condition.
[0055] Then, the sealed precursor is subjected to isobaric sintering. For example, the sealed precursor can be placed in a hot press furnace for isobaric sintering to obtain a sodium iron sulfate composite positive electrode material. During the isobaric sintering process, the material is fully compressed, the pressure on the precursor is uniform and consistent, and the pressure always exists during the reaction process, which can effectively ensure the full progress of the reaction, and can also ensure that the sodium iron sulfate and the carbon are tightly combined, so that the carbon tightly covers the sodium iron sulfate, which can effectively reduce the water absorption of the sodium iron sulfate composite positive electrode material, and effectively solve the problem that the sodium iron sulfate composite positive electrode material cannot effectively avoid water absorption due to the inability of the prior art to effectively combine the carbon and the sodium iron sulfate raw material. After the sodium iron sulfate composite positive electrode material is exposed to a drying room with a humidity of 0.01 to 0.1 ppm for 1 week, its moisture content remains below 1000 ppm; at the same time, the uniform and always existing pressure can make the sodium iron sulfate and the carbon directly and closely contact, which can reduce the gap between the sodium iron sulfate and the carbon, avoid the gap being too large to deteriorate the performance of the sodium iron sulfate composite positive electrode material, and avoid the problem of its specific surface area being too large due to the presence of carbon, so that the porosity, compaction density and specific surface area of the sodium iron sulfate composite positive electrode material are effectively improved.
[0056] Furthermore, during the isostatic sintering process, the heating rate can be 1 to 5°C / min, for example, 1°C / min, 1.8°C / min, 2.0°C / min, 2.2°C / min, 3°C / min, 4°C / min, 5°C / min or a range consisting of any two of them.
[0057] In the preparation system of the embodiment of the present invention, by adjusting the pressure, temperature and time of the isobaric sintering process, the porosity of the sodium acid iron composite positive electrode material can be effectively controlled to be 0.1% to 20%, and the crystallization performance of the sodium acid iron composite positive electrode material can be improved, ensuring that the compaction density of the sodium acid iron composite positive electrode material is 1.5 to 3 g / cm 3 , and the specific surface area of the sodium iron sulfate composite positive electrode material is 5 to 20 m 2 / g, to avoid excessive specific surface area that reduces the first coulomb efficiency and affects the performance of the sodium iron sulfate composite positive electrode material, and to improve its water absorption, first coulomb efficiency, charge and discharge specific capacity and other properties.
[0058] In order to protect the equipment and mold, the sealed precursor can be placed under inert gas for isobaric sintering (at this time, the precursor is still in a vacuum state under closed conditions). After the isobaric sintering is completed and the pressure of the reaction system is released, the reaction product is cooled to 50-150°C and then crushed and sieved to obtain the sodium iron sulfate composite positive electrode material.
[0059] The vacuum hot pressing sintering process of the prior art has poor airtightness and there is a risk of oxidation of the material to be sintered. It is necessary to maintain a vacuum during the sintering process, which increases the production cost. The precursor of the embodiment of the present invention is dried and vacuum sealed to ensure that the precursor will not be oxidized, thereby preventing the divalent iron from being oxidized to trivalent iron.
[0060] The iron source used in the embodiment of the present invention may include ferrous sulfate, such as one or more of ferrous sulfate heptahydrate, ferrous sulfate tetrahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate; the sodium source may include sodium sulfate, such as one or more of anhydrous sodium sulfate and sodium sulfate decahydrate; the conductive carbon may include one or more of conductive carbon black (Super-P), single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, redox graphene, acetylene black, Ketjen black, carbon nanofibers, and activated carbon; the antioxidant may include one or more of ascorbic acid, citric acid, tea polyphenols, and glucose. Among them, in the raw material of the sodium iron sulfate composite positive electrode material, the mass percentage of the conductive carbon may be 0.1% to 10%, and the ratio of the mass of the above antioxidant to the mass of the iron source may be 0.01% to 10%.
[0061] The embodiment of the present invention further provides a positive electrode sheet, which includes the above-mentioned sodium iron sulfate composite positive electrode material or the sodium iron sulfate composite positive electrode material obtained according to the above-mentioned preparation method. The positive electrode sheet has the technical effects corresponding to the above-mentioned sodium iron sulfate composite positive electrode material, which will not be repeated here.
[0062] The positive electrode sheet of the embodiment of the present invention specifically includes a positive electrode current collector and a positive electrode active layer formed by the above-mentioned sodium iron sulfate composite positive electrode material and arranged on the surface of the positive electrode current collector.
[0063] When preparing the positive electrode sheet, for example, the sodium iron sulfate composite positive electrode material of the embodiment of the present invention, the conductive agent and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and the mixture is fully stirred to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70-99wt% of the sodium iron sulfate composite positive electrode material, 0.5-15wt% of the conductive agent, and 0.5-15wt% of the binder according to the mass percentage, and further includes 80-98wt% of the sodium iron sulfate composite positive electrode material, 1-10wt% of the conductive agent, and 1-10wt% of the binder.
[0064] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, carbon fiber, carbon nanotubes, and conductive graphite; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.
[0065] The embodiment of the present invention further provides a sodium ion battery, which includes the above-mentioned positive electrode sheet. The sodium ion battery has the technical effects corresponding to the above-mentioned positive electrode sheet or the sodium iron sulfate composite positive electrode material, which will not be described in detail here.
[0066] It is conceivable that the sodium ion battery of the embodiment of the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.
[0067] The embodiments of the present invention do not strictly limit the negative electrode active material in the negative electrode sheet, and may be a negative electrode active material commonly used in current sodium ion batteries, such as at least one of hard carbon, soft carbon, titanium-based materials, metal oxides and sulfides.
[0068] The embodiment of the present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in the current sodium ion battery electrolyte, and the electrolyte sodium salt commonly used in the current sodium ion electrolyte, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the electrolyte may be, for example, sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, and sodium fluorotrifluoromethylsulfonylimide.
[0069] The embodiments of the present invention do not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in sodium ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, and a diaphragm with a ceramic coating.
[0070] When preparing sodium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery. After the battery is shelved, formed and sealed for the second time, the preparation of the sodium-ion battery is completed.
[0071] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0072] Example 1
[0073] This embodiment provides a method for preparing a sodium iron sulfate composite positive electrode material, comprising:
[0074] 1) drying ferrous sulfate heptahydrate at 350° C. under vacuum for 10 h to obtain anhydrous ferrous sulfate; drying sodium sulfate at 200° C. under vacuum for 10 h to obtain anhydrous sodium sulfate; using a jet mill to grind the anhydrous ferrous sulfate and anhydrous sodium sulfate to a particle size D50 of 0.8 μm, wherein the pressure of the jet mill is 1.5 MPa and the time is 10 min, and nitrogen protection is used when grinding the anhydrous ferrous sulfate;
[0075] 2) Weigh 1211g of anhydrous ferrous sulfate, 809g of anhydrous sodium sulfate, 60g of Super-P, and 121g of ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7, and premix the above materials with a high-speed mixer for 10 minutes, and nitrogen is used for protection during the premixing process; then the premixed materials are crushed and mixed by a jet mill, the airflow pressure of the jet mill is 1MPa, the time is 5min, and the atmosphere of the jet mill is nitrogen; then the jet mill crushed and mixed materials are loaded into a planetary ball mill, the ball-to-material ratio is 10:1, the rotation speed is 600rpm, and ball milling is carried out under nitrogen protection for 6 hours to obtain a precursor (positive electrode material precursor);
[0076] 3) Compact the precursor to 1.4 g / cm 3 After that, the precursor is loaded into a hot isostatic pressing mold, and then the precursor and the hot isostatic pressing mold are heated to 300°C and baked for 0.5 hours under a vacuum of 0.001Pa;
[0077] 4) After sealing the hot isostatic pressing mold, place it in a hot isostatic press, heat it to 350°C at 2°C / min, pressurize it to 10MPa at 350°C, keep it warm for 12 hours, and then cool it to 150°C. Then, take out the material from the hot isostatic pressing mold, crush and sieve it, and obtain the sodium iron sulfate composite positive electrode material.
[0078] The porosity of the sodium iron sulfate composite positive electrode material of Example 1 is 3.72%, and the compaction density is 2.48 g / cm 3 , with a specific surface area of 7.65m 2 / g, the mass percentage of sodium-rich impurity phase is 0.32%, the moisture content is 136.11ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.35ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.35ppm / h, the purity is 99.53%, the mass percentage of trivalent iron is 0.22%, the particle size of its primary particles is 382nm, and the particle size of secondary particles is 4.68μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 1, the mass percentage of secondary particles is 28.13%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 69.96%, and the mass percentage of free conductive carbon is 1.91%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 28.64%, and the mass percentage of remaining secondary particles is 71.36%.
[0079] Example 2
[0080] This embodiment is basically the same as Embodiment 1, except that:
[0081] In step 4), the pressure of the hot isotropic pressing was adjusted from 10 MPa to 20 MPa, and other conditions remained unchanged.
[0082] The porosity of the sodium iron sulfate composite positive electrode material of Example 2 is 3.12%, and the compaction density is 2.65 g / cm 3 , with a specific surface area of 6.37m 2 / g, the mass percentage of sodium-rich impurity phase is 0.24%, the moisture content is 132.36ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.31ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.26ppm / h, the purity is 99.62%, the mass percentage of trivalent iron is 0.19%, the particle size of its primary particles is 489nm, and the particle size of secondary particles is 5.62μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 2, the mass percentage of secondary particles is 31.44%, the mass percentage of primary particles that are not agglomerated to form secondary particles and exist alone is 67.21%, and the mass percentage of free conductive carbon is 1.35%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 31.27%, and the mass percentage of remaining secondary particles is 68.73%.
[0083] Example 3
[0084] This embodiment is basically the same as Embodiment 1, except that:
[0085] In step 4), the pressure of the hot isochronous pressing was adjusted from 10 MPa to 5 MPa, and other conditions remained unchanged.
[0086] The porosity of the sodium iron sulfate composite positive electrode material of Example 3 is 4.83%, and the compaction density is 2.23 g / cm 3 , with a specific surface area of 9.78m 2 / g, the mass percentage of sodium-rich impurity phase is 0.35%, the moisture content is 129.58ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 3.57ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.33ppm / h, the purity is 99.29%, the mass percentage of trivalent iron is 0.21%, the particle size of its primary particles is 361nm, and the particle size of secondary particles is 4.16μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 3, the mass percentage of secondary particles is 19.75%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 77.63%, and the mass percentage of free conductive carbon is 2.62%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 23.55%, and the mass percentage of remaining secondary particles is 76.45%.
[0087] Example 4
[0088] This embodiment is basically the same as Embodiment 1, except that:
[0089] In step 4), the temperature of hot isotropic pressing was adjusted from 350° C. to 300° C., and other conditions remained unchanged.
[0090] The porosity of the sodium iron sulfate composite positive electrode material of Example 4 is 4.03%, and the compaction density is 2.37 g / cm 3 , with a specific surface area of 8.84m 2 / g, the mass percentage of sodium-rich impurity phase is 0.41%, the moisture content is 156.27ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.32ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.45ppm / h, the purity is 99.45%, the mass percentage of trivalent iron is 0.25%, the particle size of its primary particles is 357nm, and the particle size of secondary particles is 4.37μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 4, the mass percentage of secondary particles is 27.86%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 70.29%, and the mass percentage of free conductive carbon is 1.85%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 26.51%, and the mass percentage of remaining secondary particles is 73.49%.
[0091] Example 5
[0092] This embodiment is basically the same as Embodiment 1, except that:
[0093] In step 4), the hot isostatic pressing time (holding time) was adjusted from 12 h to 8 h, and other conditions remained unchanged.
[0094] The porosity of the sodium iron sulfate composite positive electrode material of Example 5 is 3.91%, and the compaction density is 2.44 g / cm 3 , with a specific surface area of 8.21m 2 / g, the mass percentage of sodium-rich impurity phase is 0.28%, the moisture content is 146.16ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.43ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.41ppm / h, the purity is 99.37%, the mass percentage of trivalent iron is 0.24%, the particle size of its primary particles is 374nm, and the particle size of secondary particles is 4.45μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 5, the mass percentage of secondary particles is 27.61%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 70.32%, and the mass percentage of free conductive carbon is 2.07%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 26.78%, and the mass percentage of remaining secondary particles is 73.22%.
[0095] Example 6
[0096] This embodiment is basically the same as Embodiment 1, except that:
[0097] In step 2), “weigh 1244 g anhydrous ferrous sulfate (FeSO4), 776 g anhydrous sodium sulfate (Na2SO4), 60 g Super-P, 123 g ascorbic acid, wherein the sodium-iron molar ratio is 1:0.75” is used to replace “weigh 1211 g anhydrous ferrous sulfate, 809 g anhydrous sodium sulfate, 60 g Super-P, 121 g ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7”, and other conditions remain unchanged.
[0098] The porosity of the sodium iron sulfate composite positive electrode material of Example 6 is 3.85%, and the compaction density is 2.51 g / cm 3 , with a specific surface area of 7.85m 2 / g, the mass percentage of sodium-rich impurity phase is 0.53%, the moisture content is 131.65ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 3.86ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.28ppm / h, the purity is 99.51%, the mass percentage of trivalent iron is 0.31%, the particle size of its primary particles is 396nm, and the particle size of secondary particles is 4.87μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 6, the mass percentage of secondary particles is 29.33%, the mass percentage of primary particles that are not agglomerated to form secondary particles and exist alone is 68.83%, and the mass percentage of free conductive carbon is 1.84%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 27.49%, and the mass percentage of remaining secondary particles is 72.51%.
[0099] Example 7
[0100] This embodiment is basically the same as Embodiment 1, except that:
[0101] In step 2), “weigh 1294 g anhydrous ferrous sulfate (FeSO4), 726 g anhydrous sodium sulfate (Na2SO4), 60 g Super-P, 129 g ascorbic acid, wherein the sodium-iron molar ratio is 1:0.833;” is used to replace “weigh 1211 g anhydrous ferrous sulfate, 809 g anhydrous sodium sulfate, 60 g Super-P, 121 g ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7,” and other conditions remain unchanged.
[0102] The porosity of the sodium iron sulfate composite positive electrode material of Example 7 is 3.82%, and the compaction density is 2.54 g / cm 3 , with a specific surface area of 7.96m 2 / g, the mass percentage of sodium-rich impurity phase is 0.47%, the moisture content is 135.91ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 3.69ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.26ppm / h, the purity is 99.23%, the mass percentage of trivalent iron is 0.38%, the particle size of its primary particles is 403nm, and the particle size of secondary particles is 4.91μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 7, the mass percentage of secondary particles is 30.28%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 67.98%, and the mass percentage of free conductive carbon is 1.74%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 27.02%, and the mass percentage of remaining secondary particles is 72.98%.
[0103] Example 8
[0104] This embodiment is basically the same as Embodiment 1, except that:
[0105] In step 4), replace “4) Then seal the hot isostatic pressing mold, put it into a hot isostatic press, heat it to 400°C at 2.2°C / min, pressurize it to 1MPa at 400°C, keep it warm for 24h, then cool it to 150°C, take out the material from the hot isostatic pressing mold, crush and sieve it to obtain a sodium iron sulfate composite positive electrode material” with “Then seal the hot isostatic pressing mold, put it into a hot isostatic press, heat it to 350°C at 2°C / min, pressurize it to 10MPa at 350°C, keep it warm for 12h, then cool it to 150°C, take out the material from the hot isostatic pressing mold, crush and sieve it to obtain a sodium iron sulfate composite positive electrode material”, and other conditions remain unchanged.
[0106] The porosity of the sodium iron sulfate composite positive electrode material of Example 8 is 5.36%, and the compaction density is 2.13 g / cm 3 , with a specific surface area of 10.23m 2 / g, the mass percentage of sodium-rich impurity phase is 0.68%, the moisture content is 176.36ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.52ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.48ppm / h, the purity is 97.14%, the mass percentage of trivalent iron is 1.67%, the particle size of its primary particles is 768nm, and the particle size of secondary particles is 5.52μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 8, the mass percentage of secondary particles is 17.39%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 79.64%, and the mass percentage of free conductive carbon is 2.97%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 18.38%, and the mass percentage of remaining secondary particles is 81.62%.
[0107] Example 9
[0108] This embodiment is basically the same as Embodiment 1, except that:
[0109] In step 4), replace “4) then seal the hot isostatic pressing mold, place it in a hot isostatic press, heat it to 300°C at 1.8°C / min, pressurize it to 500MPa at 300°C, keep it warm for 1h, then cool it to 150°C, take out the material from the hot isostatic pressing mold, crush and sieve it to obtain a sodium iron sulfate composite positive electrode material” with “then seal the hot isostatic pressing mold, place it in a hot isostatic press, heat it to 350°C at 2°C / min, pressurize it to 10MPa at 350°C, keep it warm for 12h, then cool it to 150°C, take out the material from the hot isostatic pressing mold, crush and sieve it to obtain a sodium iron sulfate composite positive electrode material”, and other conditions remain unchanged.
[0110] The porosity of the sodium iron sulfate composite positive electrode material of Example 9 is 2.43%, and the compaction density is 2.86 g / cm 3 , with a specific surface area of 5.23m 2 / g, the mass percentage of sodium-rich impurity phase is 0.98%, the moisture content is 138.23ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 3.73ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.24ppm / h, the purity is, the mass percentage of trivalent iron is 0.53%, the particle size of its primary particles is 935nm, and the particle size of secondary particles is 8.74μm; in addition, in the sodium iron sulfate composite positive electrode material of Example 9, the mass percentage of secondary particles is 38.51%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 61.06%, and the mass percentage of free conductive carbon is 0.43%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 39.12%, and the mass percentage of remaining secondary particles is 60.88%.
[0111] Comparative Example 1
[0112] This comparative example provides a method for preparing a sodium iron sulfate composite positive electrode material, comprising:
[0113] 1) drying ferrous sulfate heptahydrate at 350° C. under vacuum for 10 h to obtain anhydrous ferrous sulfate; drying sodium sulfate at 200° C. under vacuum for 10 h to obtain anhydrous sodium sulfate; using a jet mill to grind the anhydrous ferrous sulfate and anhydrous sodium sulfate to a particle size D50 of 0.8 μm, wherein the pressure of the jet mill is 1.5 MPa and the time is 10 min, and nitrogen protection is used when grinding the anhydrous ferrous sulfate;
[0114] 2) Weigh 1211g of anhydrous ferrous sulfate, 809g of anhydrous sodium sulfate, 60g of Super-P, and 121g of ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7, and premix the above materials with a high-speed mixer for 10 minutes, and nitrogen is used for protection during the premixing process; then the premixed materials are crushed and mixed by a jet mill, the airflow pressure of the jet mill is 1MPa, the time is 5min, and the atmosphere of the jet mill is nitrogen; then the jet mill crushed and mixed materials are loaded into a planetary ball mill, the ball-to-material ratio is 10:1, the rotation speed is 600rpm, and ball milling is carried out under nitrogen protection for 6 hours to obtain a precursor (positive electrode material precursor);
[0115] 3) The precursor is placed in a tubular furnace for sintering at a temperature of 350° C. for 12 h, and then cooled to 150° C., crushed and sieved to obtain a sodium iron sulfate composite positive electrode material.
[0116] The porosity of the sodium iron sulfate composite positive electrode material of Comparative Example 1 is 8.87%, and the compaction density is 1.89 g / cm 3 , with a specific surface area of 15.76m 2 / g, the mass percentage of sodium-rich impurity phase is 5.85%, the moisture content is 1487.69ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 9.81ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 6.93ppm / h, the purity is 92.36%, the mass percentage of trivalent iron is 1.61%, the particle size of its primary particles is 326nm, and the particle size of the secondary particles is 3.95μm; in addition, in the sodium iron sulfate composite positive electrode material of Comparative Example 1, the mass percentage of secondary particles is 16.97%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 78.36%, and the mass percentage of free conductive carbon is 4.12%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 7.36%, and the mass percentage of the remaining secondary particles is 92.64%.
[0117] Comparative Example 2
[0118] This comparative example provides a method for preparing a sodium iron sulfate composite positive electrode material, comprising:
[0119] 1) drying ferrous sulfate heptahydrate at 350° C. under vacuum for 10 h to obtain anhydrous ferrous sulfate; drying sodium sulfate at 200° C. under vacuum for 10 h to obtain anhydrous sodium sulfate; using a jet mill to grind the anhydrous ferrous sulfate and anhydrous sodium sulfate to a particle size D50 of 0.8 μm, wherein the pressure of the jet mill is 1.5 MPa and the time is 10 min, and nitrogen protection is used when grinding the anhydrous ferrous sulfate;
[0120] 2) Weigh 1211g of anhydrous ferrous sulfate, 809g of anhydrous sodium sulfate, 60g of Super-P, and 121g of ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7, and premix the above materials with a high-speed mixer for 10 minutes, and nitrogen is used for protection during the premixing process; then the premixed materials are crushed and mixed by a jet mill, the airflow pressure of the jet mill is 1MPa, the time is 5min, and the atmosphere of the jet mill is nitrogen; then the jet mill crushed and mixed materials are loaded into a planetary ball mill, the ball-to-material ratio is 10:1, the rotation speed is 600rpm, and ball milling is carried out under nitrogen protection for 6 hours to obtain a precursor (positive electrode material precursor);
[0121] 3) Compact the precursor to 1.4 g / cm 3 After that, it was loaded into a hot isostatic pressing mold, and then the temperature was raised to 350°C at 2°C / min, and then pressurized to 10MPa at 350°C and kept warm for 12 hours. After that, it was cooled to 150°C, and the material was taken out of the hot isostatic pressing mold, crushed and sieved to obtain the sodium iron sulfate composite positive electrode material.
[0122] The porosity of the sodium iron sulfate composite positive electrode material of Comparative Example 2 is 6.31%, and the compaction density is 2.23 g / cm 3 , with a specific surface area of 11.83m 2 / g, the mass percentage of sodium-rich impurity phase is 1.14%, the moisture content is 655.28ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 5.72ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 3.67ppm / h, the purity is 98.34%, the mass percentage of trivalent iron is 0.81%, the particle size of its primary particles is 376nm, and the particle size of secondary particles is 4.71μm; in addition, in the sodium iron sulfate composite positive electrode material of Comparative Example 2, the mass percentage of secondary particles is 28.25%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 69.87%, and the mass percentage of free conductive carbon is 1.88%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 28.57%, and the mass percentage of remaining secondary particles is 71.83%.
[0123] Comparative Example 3
[0124] This comparative example is basically the same as Example 1, except that:
[0125] Step 2) is adjusted to "weigh 1211g of anhydrous ferrous sulfate, 809g of anhydrous sodium sulfate, 60g of Super-P, and 121g of ascorbic acid, wherein the sodium-iron molar ratio is 1:0.7, and the above materials are premixed with a high-speed mixer for 10 minutes, and nitrogen is used for protection during the premixing process; then the premixed materials are crushed and mixed by a jet mill, the airflow pressure of the jet mill is 1MPa, the time is 5min, and the atmosphere of the jet mill is nitrogen; obtain a precursor (positive electrode material precursor);", and other conditions remain unchanged.
[0126] The porosity of the sodium iron sulfate composite positive electrode material of Comparative Example 3 is 3.95%, and the compaction density is 2.41 g / cm 3 , with a specific surface area of 8.65m 2 / g, the mass percentage of sodium-rich impurity phase is 4.57%, the moisture content is 133.85ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.63ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.29ppm / h, the purity is 93.67%, the mass percentage of trivalent iron is 2.23%, the particle size of its primary particles is 1363nm, and the particle size of the secondary particles is 15.32μm; in addition, in the sodium iron sulfate composite positive electrode material of Comparative Example 3, the mass percentage of secondary particles is 13.68%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 82.46%, and the mass percentage of free conductive carbon is 3.21%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 14.39%, and the mass percentage of the remaining secondary particles is 85.61%.
[0127] Comparative Example 4
[0128] This comparative example is basically the same as Example 1, except that:
[0129] In step 1), "the anhydrous ferrous sulfate and anhydrous sodium sulfate are respectively ground into a particle size of 1.5 μm using a jet mill".
[0130] The porosity of the sodium iron sulfate composite positive electrode material of Comparative Example 4 is 3.87%, and the compaction density is 2.56 g / cm 3 , with a specific surface area of 8.01m 2 / g, the mass percentage of sodium-rich impurity phase is 3.31%, the moisture content is 136.83ppm, the rate of increase of moisture content in an atmosphere with a humidity of 0.1-0.5ppm is 4.52ppm / h, and the rate of increase of moisture content in an atmosphere with a humidity of less than 0.1ppm is 2.32ppm / h, the purity is 95.82%, the mass percentage of trivalent iron is 1.38%, the particle size of its primary particles is 1867nm, and the particle size of the secondary particles is 19.58μm; in addition, in the sodium iron sulfate composite positive electrode material of Comparative Example 4, the mass percentage of secondary particles is 14.76%, the mass percentage of primary particles that exist alone without agglomeration to form secondary particles is 82.03%, and the mass percentage of free conductive carbon is 3.21%; in the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon is 14.39%, and the mass percentage of the remaining secondary particles is 85.61%.
[0131] Test Example 1
[0132] The following parameters of the sodium iron sulfate composite positive electrode material of each embodiment and comparative example were tested:
[0133] 1) Porosity: The porosity can be detected by specific surface area (BET) combined with void analysis.
[0134] 2) Compaction density: Use automatic compaction density detection equipment for detection.
[0135] 3) Specific surface area: The specific surface area was measured using the Best method.
[0136] 4) Moisture content and rate of increase of moisture content: The moisture content was tested by using the Karl Fischer method. Samples were taken for testing every 1 day for 7 times, and the average rate of increase of moisture content was calculated.
[0137] 5) Chemical formula and purity of sodium ferric sulfate composite positive electrode material: The chemical formula of the sodium ferric sulfate composite positive electrode material is obtained by inductively coupled plasma emission spectroscopy (ICP analysis) of the contents of various elements; the purity of the sodium ferric sulfate composite positive electrode material is calculated using the contents of various elements.
[0138] 6) Mass percentage of trivalent iron: detected by chemical titration method.
[0139] 7) Mass percentage of sodium-rich impurity phase: The sodium-rich impurity phase content was calculated using the refined X-ray diffraction analysis (XRD) pattern with the aid of Jade software.
[0140] 8) Particle size of secondary particles and particle size of primary particles: The particle size of secondary particles and particle size of primary particles were directly measured in a scanning electron microscope (SEM) image.
[0141] 9) In the sodium ferric sulfate composite positive electrode material, the mass percentage of secondary particles, the mass percentage of primary particles that exist alone without agglomerating to form secondary particles, and the mass percentage of free conductive carbon: first, the sample (sodium ferric sulfate composite positive electrode material) is centrifuged to separate the free conductive carbon, the mass of the free conductive carbon is weighed, and the mass percentage of the free conductive carbon is calculated; then, the number of primary particles and the number of secondary particles are counted in the scanning electron microscope (SEM) image, and their particle sizes are measured respectively. Then, the volume of all primary particles and secondary particles can be calculated. Since the densities of primary particles and secondary particles are approximately equal, the volume ratio is calculated first, and then the mass percentage can be calculated.
[0142] 10) Among the secondary particles, the mass percentage of secondary particles formed by agglomeration of primary particles connected by conductive carbon, and the mass percentage of remaining secondary particles: Secondary particles are selected for cross-sectional analysis. The number of the two types of secondary particles mentioned above can be directly counted by transmission electron microscopy (TEM), and then calculated based on statistical principles.
[0143] Test results
[0144] Table 1
[0145]
[0146] Table 2
[0147]
[0148]
[0149] Data Analysis:
[0150] Figure 4 is the sodium ferric sulfate (Na 2.5 Fe 1.75 XRD pattern of (SO4)3); Figure 4 The horizontal axis is 2Theta (degree) (i.e. the diffraction angle 2θ), and the vertical axis is Intensity (au) (i.e. the intensity of the diffraction peak);
[0151] Figure 5 The XRD diagram of the sodium-rich impurity phase (Na6Fe(SO4)4) in the sodium ferric sulfate in Comparative Example 1; Figure 5 The horizontal axis is 2Theta (degree) (i.e., the diffraction angle 2θ), and the vertical axis is Intensity (au) (i.e., the intensity of the diffraction peak); Figure 5 It can be seen that the dotted box is the sodium-rich impurity phase Na6Fe(SO4)4. This impurity phase is currently difficult to completely remove, but its content can be kept at a low level by adjusting the raw material ratio and process parameters. What can be determined at present is that if its content is too high, the electrochemical performance of the sample will be greatly reduced. However, some literature points out that this phase will form a heterojunction with the target sodium ferric sulfate phase, which will promote the transmission of sodium ions, but further verification is needed. In addition, this phase is very easy to appear in the process of preparing sodium ferric sulfate with high iron content by conventional methods. By using hot isostatic pressing, high-iron sodium ferric sulfate with low sodium-rich impurity content can be prepared.
[0152] Test Example 2
[0153] The sodium iron sulfate composite positive electrode materials of the embodiment and the comparative example are respectively made into positive electrode sheets, and then assembled with negative electrode sheets, electrolytes and separators according to the following method to obtain button batteries. The method includes:
[0154] Each sodium iron sulfate composite positive electrode material was mixed with conductive carbon black (SP) and PVDF in a weight ratio of 80%:10%:10% to obtain a positive electrode slurry by dispersion. The positive electrode slurry was coated on an aluminum foil current collector and rolled to obtain a surface density of 7.8 g / cm 3The positive electrode sheet is then punched out into a small disc with a diameter of 12 mm using a film mold. After drying and weighing, a button battery is assembled in a glove box under an Ar protective atmosphere using a 2025 button battery shell, metallic sodium as the negative electrode, an electrolyte solvent: ethylene carbonate and propylene carbonate solvent in a volume ratio of 1:1, and an electrolyte salt: 1 mol / L sodium hexafluorophosphate.
[0155] After each button cell was allowed to stand at 25°C for 4 hours, the first charge and discharge capacity test was carried out. The test conditions were as follows: charge at 0.1C to 4.5V, charge at constant voltage to 0.025C and then cut off. After standing for 3 minutes, discharge at 0.1C to 2.0V, obtain the charge and discharge curve, and record the first charge capacity in grams C0 and the first discharge capacity in grams D0 from 2 to 4.5V, respectively. The first coulombic efficiency was calculated according to D0 / C0.
[0156] Test results
[0157] Table 3
[0158] serial number 0.1C charging capacity mAh / g 0.1C discharge capacity mAh / g First coulombic efficiency % Example 1 108.13 99.08 91.63 Example 2 106.16 97.50 91.84 Example 3 107.74 98.52 91.44 Example 4 108.49 98.39 90.69 Example 5 106.92 97.85 91.52 Example 6 109.54 101.24 92.43 Example 7 113.16 104.31 92.18 Example 8 98.67 89.69 90.89 Example 9 102.38 93.46 91.29 Comparative Example 1 93.21 83.51 90.67 Comparative Example 2 96.13 87.12 90.62 Comparative Example 3 72.95 65.52 89.81 Comparative Example 4 86.39 71.23 82.45
[0159] Combined with the above table, Figure 1 , Figure 2 and Figure 3 Perform data analysis:
[0160] The electrochemical performance of the sodium iron sulfate composite positive electrode material of the embodiment of the present invention is good; the precursor of comparative example 1 is sintered at normal pressure in a tubular furnace, and the contact between the materials during the sintering process is not sufficient, the atomic diffusion energy barrier is high, the reaction between the phases is insufficient, and even some of them cannot react, resulting in poor electrochemical performance of the sodium iron sulfate composite positive electrode material. Even if the precursor of comparative example 2 is pre-pressed (compacted) before sintering, although the contact degree between the materials is increased to a certain extent, when the pressure is released, the material will rebound, causing the contact tightness of the material to decrease, and in the subsequent sintering process, the residual moisture in the material itself and the moisture, carbon dioxide, etc. generated by the decomposition of the additive will be discharged, resulting in a decrease in the contact tightness between the materials. Even if hot pressing sintering is used, the materials can be in close contact during the sintering process, the diffusion energy barrier can be reduced, and the reaction between the materials is beneficial, but the pressure on the material is unidirectional pressure, and the pressure on the materials at different positions is inconsistent, resulting in poor electrochemical performance of the sodium iron sulfate composite positive electrode material.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium iron sulfate composite positive electrode material, characterized in that: The porosity of the sodium iron sulfate composite positive electrode material is 0.1% to 10%, and the compaction density is 2.1 to 3 g / cm 3 , and the specific surface area of the sodium iron sulfate composite positive electrode material is 5 to 12 m 2 / g, and the mass percentage of the sodium-rich impurity phase in the sodium iron sulfate composite positive electrode material is 0.1% to 1%.
2. The sodium iron sulfate composite positive electrode material according to claim 1, characterized in that: In an atmosphere with a humidity of 0.1 to 0.5 ppm, the rate of increase of the water content of the sodium iron sulfate composite positive electrode material is less than 5.5 ppm / h; in an atmosphere with a humidity of less than 0.1 ppm, the rate of increase of the water content of the sodium iron sulfate composite positive electrode material is less than 2.5 ppm / h; And / or, the mass percentage of trivalent iron in the sodium iron sulfate composite positive electrode material is less than 1%; And / or, the mass percentage of impurities in the sodium iron sulfate composite positive electrode material is less than 5%.
3. The sodium iron sulfate composite positive electrode material according to claim 1, characterized in that: The chemical formula of the sodium iron sulfate composite positive electrode material is Na 2+2x Fe 2-x (SO4)3@C, where 0≤x<2.
4. The sodium iron sulfate composite positive electrode material according to claim 1, characterized in that: The particle size of the primary particles of the sodium iron sulfate composite positive electrode material is 50 to 1000 nm, and some of the primary particles are agglomerated to form secondary particles, and the particle size of the secondary particles is 1 to 10 μm; In the sodium iron sulfate composite positive electrode material, the mass percentage of the secondary particles is 15% to 40%, and the mass percentage of the remaining primary particles is 60% to 85%.
5. The sodium iron sulfate composite positive electrode material according to claim 4, characterized in that: The sodium iron sulfate composite positive electrode material also includes conductive carbon; Among the secondary particles, some of the secondary particles are formed by agglomeration of the primary particles connected by the conductive carbon, the mass percentage of the some of the secondary particles in the secondary particles is 15% to 40%, and the mass percentage of the remaining part of the secondary particles in the secondary particles is 60% to 85%.
6. A method for preparing the sodium iron sulfate composite positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The iron source and the sodium source are crushed to a particle size of less than 1 μm respectively; The crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant are mixed to obtain a precursor; The precursor is dried under vacuum conditions, the dried precursor is sealed to ensure that the precursor is under vacuum conditions, and then the sealed precursor is isobaric sintered, the isobaric sintering pressure is 1 to 500 MPa, the temperature is 300 to 400° C., and the time is 1 to 24 hours to obtain the sodium iron sulfate composite positive electrode material.
7. The method for preparing the sodium iron sulfate composite positive electrode material according to claim 6, characterized in that: The process of mixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant to obtain the precursor includes: premixing the crushed iron source, the crushed sodium source, the conductive carbon and the antioxidant, crushing and mixing them again by air flow mill or rolling ball mill, and finally performing solid solution mixing by planetary ball mill or vibration ball mill to obtain the precursor; And / or, the isostatic sintering includes hot isostatic pressing sintering or spark plasma sintering; And / or, during the isostatic sintering process, the heating rate is 1-5° C. / min.
8. The method for preparing the sodium iron sulfate composite positive electrode material according to claim 6, characterized in that: The iron source includes ferrous sulfate; and / or, the sodium source comprises sodium sulfate; And / or, the conductive carbon includes one or more of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, redox graphene, acetylene black, Ketjen black, carbon nanofibers, and activated carbon; And / or, the antioxidant includes one or more of ascorbic acid, citric acid, tea polyphenols, and glucose; the ratio of the mass of the antioxidant to the mass of the iron source is 0.01% to 10%.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the sodium iron sulfate composite positive electrode material according to any one of claims 1 to 5 or the sodium iron sulfate composite positive electrode material obtained according to the preparation method according to any one of claims 6 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Positive pole piece and battery
CN115312684A
Preparation method of sodium ferrous sulfate / carbon composite positive electrode material, positive electrode material, positive electrode plate and sodium ion battery
CN117154062A
Positive electrode material, preparation method thereof and sodium ion battery
CN117577831A
Sodium ferric sulfate positive electrode material and preparation method and application thereof
CN117800400A
Preparation method of low-porosity polyanion type secondary battery positive electrode material
CN118221093A
Cited By
Modified sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN121449109A
Sodium iron sulfate-based composite positive electrode material, and preparation method therefor and use thereof
WO2026066501A1